THE ROLE OF BAITUL MAAL WAT TAMWIL IN ACHIEVE SUSTAINABLE DEVELOPMENT GOALAS (CASE STUDY OF BMT BANGUN RAKYAT SEJAHTERA) - Apriani, Tetty (Jurnal Ekonomi Balance, 2021)
Prosperity is a condition that is dreamed of by every human being.  However, in practice, conditions of prosperity are very difficult to achieve.  Many factors become obstacles in achieving prosperity.  One of the efforts to achieve prosperity is to support sustainable development goals (SDGs).  BMT is one of the institutions that is starting to grow for economic recovery in Indonesia for that BMT can help realize the goals of the SDGs.  The purpose of this study is to find out how the role of BMT in achieving sustainable development goals. This research is qualitative research which consists of data reduction, data presentation and finally drawing conclusions.  With the object of research, namely BMT Bina Rakyat Sejahtera.  The source of data in this study is primary data, namely data obtained directly from the BMT BRS management through interviews. The results of the qualitative analysis show that there are 8 SDGs objectives that have been implemented by BMT BRS.  The eight goals are zero poverty, no hunger, good health and well-being for all at all ages, quality education, gender equality, clean water and sanitation, economic growth and decent work, and industry, innovation and infrastructure.